Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Tagungsbericht: Unverfügbarkeit – Widmung – Latenz: Das Heilige in der Kultur. Interdisziplinäre Tagung vom 16. bis 18. November 2021 an der Universität Paderborn - Becker, Rieke; Lauert, Markus; Fischer, Jessica; Kirchhoff, Hannah; Kornbach, Alina; Januschewski, Katharina

Experimental Measurement Method and Evaluation of an Analytical Approach for Sound Conduction through Multiple Clinched Sheets - Stephan, Richard; Brosius, Alexander (The 28th Saxon Conference on Forming Technology SFU and the 7th International Conference on Accuracy in Forming Technology ICAFT)
The conduction of structure-borne sound through joints causes energy dissipation. The sound reduction index describes this energy loss as a level decrease in the particle velocity across series-connected damping elements for which the superposition principle applies. This simple model can help to develop a testing method for joints based on this characteristic energy loss. In this paper, this model is experimentally evaluated for multiple in-series clinched aluminium sheets. Samples connected by several clinch points arranged in parallel are investigated experimentally, and the results are discussed.
Keywords: clinching; mechanical joining; damping; model; evaluation; dynamics

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Experimental and Numerical Analysis of Cold Formed Multi Pin Structures Using a Multi-Acting Tool Design - Römisch, David; Merklein, Marion

Versatile tool design for a tumbling self-piercing riveting process - Wituschek, Simon; Lechner, Michael

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

Die Kraft der Bilder. Funktionen neuer Illustrationen bei Übersetzungen. Kathleen Vereecken – Alles komt goed, altijd (2018) | Alles wird gut, immer (2021) - Lammer, Christina
Keywords: Kathleen Vereecken; Kinder- und Jugendliteratur; Krieg; Belgien

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Von lebenden Systemen und gefühlten Zahlen. Eine körpersoziologische Analyse des finanzaufsichtlichen Risikobewertungsregimes - Knoll, Lisa (Österreichische Zeitschrift für Soziologie)
Der hier vorliegende Beitrag erarbeitet Verbindungslinien zwischen Wirtschaftssoziologie (insb. Finanzsoziologie), Soziologie der Bewertung und Körpersoziologie anhand des Falls finanzmarktregulatorischer Risikobewertung. Dabei spielt der analytische Begriff der Prothese (Michel Callon) eine wichtige Rolle. Nach der Finanzkrise kommt es zu einer Neuverteilung von sensorischen Bewertungskompetenzen in einer hierarchisch aufgebauten, vernetzten Wissensarchitektur. Es ist nun die Maschine, der Lebendigkeit attestiert wird, während der Mensch parzellierte Funktionen in einer Apparatur übernimmt. Gleichzeitig soll der Mensch so zu einem adäquaten und beweglichen (spielerischen) Umgang mit Risiken angeregt werden, die man ihm/ihr in einem eher groben und einfachen Aufsichtssystem nicht mehr zutraute (hier wurden „regulatory arbitrage“ und „kreative Buchführung“ zum Problem). Der Aufsatz rekonstruiert die praktischen Orientierungen und kollektiven Erfahrungen dieses finanzaufsichtlichen Umbaus anhand zweier problemzentrierter Interviews. Unter Rekurs auf die Körperbezüge in diesen Interviews wird die Paradoxie eines Systems herausgearbeitet, das nach wie vor auf individuelle Entscheidungsrationalität und -agilität setzt, diese nun aber maschinell zu erschaffen sucht.
Keywords: General Social Sciences

Zweierlei Homophilie: Wendy Hui Kyong Chun und Leo Bersani - Althoff, Sebastian (Mimesis Expanded: Die Ausweitung der mimetischen Zone)

Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Ich. Das bin ich! Zugehörigkeit, Freundschaft und Familie. Zyklus 2 - Tenberge, Claudia; von Braunmühl, Susanne